Materialism: Construct Conceptualisation and Operationalisation - Mishra, Manit (Indian Journal of Marketing, 2010)
The concept of materialism as an inherent constituent of consumer lifestyle is a profoundly dialectical construct. The issue has been of interest to a range of homo-sapiens - from the dilettante who have dabbled in its aura to the prophets whose homilies have castigated it as a source of retrogression towards spiritual bankruptcy. Materialism is indeed an eclectic notion which finds a mention in an entire gamut of disciplines. The bouquets and brickbats notwithstanding, the issue is a livewire and deserves profound investigation. In this era of glasnost and perestroika in India, and given the chronologically conspicuous conundrum that materialism has been in Indian culture, this was an opportune moment to explore the conceptualization and operationalisation of the construct materialism.